Odpowiedź :
Hej!
a)
-2a + b - a - 2b + 3a =
= -2a - a + 3a + b - 2b = -b
b)
-ab + b² + 3ab - 2ab =
= b² - ab + 3ab - 2ab = b²
c)
2/3x + 1/3y + 2 i 1/3x - 1/3y =
= 2/3x + 2 i 1/3x + 1/3y - 1/3y = 3x
d)
15xy - 4x + 8y - 6xy + 5x - xy =
= 15xy - 6xy - xy - 4x + 5x + 8y =
= 8xy + x + 8y
e)
0,2x² - 2y + 1,8² + 4,3y - x =
= 0,2x² - 2y + 4,3y - x + 3,64 =
= 0,2x² + 2,3y - x + 3,64
f)
-1/4m + 1/8n - 1/8m + 0,375m =
= -0,25m + 0,125n - 0,125m + 0,375m =
= -0,25m - 0,125n + 0,375m + 0,125n =
= -0,375m + 0,375m + 0,125n = 0,125n
Pozdrawiam! - Julka
Odpowiedź:3
a) -2a + b - a - 2b + 3a = -3a + 3a + b = -b
b) -ab + b² + 3ab - 2ab = 3ab - 3ab + b2 = b2
c) 2/3x + 1/3y + 2 1/3x - 1/3y = 2/3x + 1/3y + 7/3x - 1/3y = 9/3x
d) 15xy - 4x + 8y - 6xy + 5x - xy = 8xy + x + 8y
e) 0,2x² - 2y + 1,8² + 4,3y - x = 0,2x2 - 2y + 4,3y - x + 3,64 = 0,2x2 +2,3y - x + 3,64
f) -1/4m + 1/8n - 1/8m + 0,375m = -0,25m + 0,125n - 0,125m + 0,375m = -0,25m - 0,125n + 0,375m + 0,125n = 0,125n